Accuracy of an OTA System Emulating a Realistic 3D Environment for GNSS and Multi-Satellite Receiver Testing - Heuberger, Albert; et al. (IEEE 8th Sensor Array and Multichannel Signal Processing Workshop (SAM), 2014)
In satellite-based systems, such as global navigation satellite systems (GNSS), the use of antenna arrays is becoming increasingly common, as it allows various applications, such as jammer/spoofer suppression or improving the positioning accuracy in multipath-environments. Testing such equipment under realistic and reproducible conditions is often not feasible, for example in the case of a not fully deployed system (e. g., Galileo satellites) or testing of classified transmission technologies (e. g., Galileo public regulated service (PRS) receivers). For tests under reproducible and realistic conditions, we propose 3D wave-field synthesis (WFS) in an over-the-air testbed. This allows a realistic emulation of the radio environment under laboratory conditions. In this paper, a feasibility study for such a testbed is presented. Possible antenna setups for a 3D WFS laboratory environment are proposed. For these setups, the 3D WFS accuracy is investigated for emulating different polarization types and multipath reflections with arbitrary source directions. The results show that with presently available hardware for channel emulation and 3D WFS, a virtual electromagnetic environment can be created for testing receivers with (beamforming) antenna arrays of typical size (120 mm-300mm diameter). © 2014 IEE
UnivIS-Import:2015-04-16:Pub.2014.tech.IE.komele.accura
Keywords: anechoic chamber; GNSS; MIMO; over - The-air testing; polarization; signal processing; testing; Wave-field synthesis